Preclinical approaches in regenerative medicine for treating end-stage renal disease: a scoping review - Vigezzi, Andrea; Brani, Paola; Dalla Gasperina, Daniela; Azzi, Lorenzo; Giaroni, Cristina; Inversini, Davide; Pettinato, Giuseppe; Massaad, Matthew; Carcano, Giulio; Ietto, Giuseppe; Baj, Andreina (Frontiers in Endocrinology, 2025)
A scoping review was conducted to systematically assess the current evidence and emerging applications of regenerative medicine in the treatment of End Stage Renal Disease (ERSD), aiming to map existing knowledge and identify key research gaps. ESRD represents a major global health burden, and despite being managed primarily through dialysis and kidney transplantation, both approaches are limited by morbidity, mortality, and organ donor shortages. Regenerative medicine emerged as a promising alternative, leveraging stem cells technologies and tissue engineering to develop functional renal tissues with the potential to restore or replace damaged kidney structures. Our review protocol was developed in accordance with the PRISMA-ScR guidelines and was prospectively registered on Figshare. Inclusion criteria comprised peer-reviewed articles published between 2004 and 2024, focusing on bioengineering strategies relevant to kidney regeneration and ESRD, with no restrictions on language or geographic origin. Editorials, letters, and non–peer-reviewed sources were excluded. A comprehensive literature search was performed in Medline, Scopus, and Web of Science using pre-defined search terms. Screening and selection were conducted independently by four reviewers working in pairs selected with discrepancies resolved through consensus. A standardized data extraction form was iteratively developed and piloted to collect relevant information on study characteristics and experimental models. Of the 5,869 records initially identified, 111 studies met the inclusion criteria. The findings underscore the therapeutic potential of regenerative medicine in ESRD, with kidney organoids and organ-on-a-chip platforms representing two of the most advanced and translationally relevant approaches currently under investigation. These technologies are increasingly recognized not only for their role in disease modeling and drug screening, but also as potential precursors to fully bioengineered renal replacement therapies.